Structure and performance of vegetable marketing in East Shoa Zone, Oromia Region, Ethiopia - Hailegiorgis, D.S.; Hagos, Fitsum (2016)
Analysis of marketing performance of vegetable plays an important role in an ongoing or future market development plan. The study primarily examines market structure of major actors and assessing the market performance for key vegetable marketing actors and channels by quantifying costs and profit margins. The data was generated by household survey using pre-tested structured questionnaires. This was supplemented by secondary data collected from different published and unpublished sources. The study result shows that the total gross marketing margin was 30% with producer participation margin of 70% implying higher marketing margin of smallholder producers. The market intermediaries incurred different marketing costs such as costs of packing, sorting, transportation, loading and unloading. Central wholesalers obtain relatively highest profit in channel numbered II and III, which amounted to Birr 204,827 and 58,675, respectively. The study result signifies that the first four largest volumes of vegetable purchased by first four big traders (CR4) constitute 50% of market share, which indicates the market structure for vegetable is strongly oligopolistic. OLS regression results also revealed that there are economies of scale for wholesalers at Meki market, which clearly indicates the presence of barrier to entry/exit for wholesalers in the market. Policy implications drawn from the study indicate that changing oligopolistic market structure, capacitating unions to supply inputs and outputs and supporting actors involved in local vegetable markets.